A light in the dark: The benefits of co-production in service failures - Pacheco Natália Araújo; Braz Becker Larissa Carine; Brei Vinícius Andrade (Elsevier, 2022)
Co-production is increasingly common but, at the same time, services failures are inevitable. Considering that previous studies are controversial about the effects of failed co-produced services, the goal of this research is to investigate the influence of co-production on causal locus attribution, in addition to emotional and attitudinal outcomes. Two experimental studies show that co-production reduces the self-serving bias, a result that brings implications for the services literature and practice. In addition to the positive effects of co-production, evidenced by previous studies, this research shows that companies and customers can benefit from co-production even when failures occur.